Enabling digital pathology in the diagnostic setting: navigating through the implementation journey in an academic medical centre. Issue 9 (12th February 2016) - Cheng, Chee Leong; Azhar, Rafay; Sng, Shi Hui Adeline; Chua, Yong Quan; Hwang, Jacqueline Siok Gek; Chin, Jennifer Poi Fun; Seah, Waih Khuen; Loke, Janel Chui Ling; Ang, Roy Hang Leng; Tan, Puay Hoon
Abstract : Aims: As digital pathology (DP) and whole slide imaging (WSI) technology advance and mature, there is an increasing drive to incorporate DP into the diagnostic environment. However, integration of DP into the diagnostic laboratory is a non-trivial task and filled with unexpected challenges unlike standalone implementations. We share our journey of implementing DP in the diagnostic laboratory setting, highlighting seven key guiding principles that drive the progression through implementation into deployment and beyond. Methods: The DP implementation with laboratory information system integration was completed in 8 months, including validation of the solution for diagnostic use in accordance with College of American Pathologists guidelines. We also conducted prospective validation via paired delivery of glass slides and WSI to our pathologists postdeployment. Results: Common themes in our guiding principles included emphasis on workflow and being comprehensive in the approach, looking beyond pathologist user champions and expanding into an extended project team involving laboratory technicians, clerical/data room staff and archival staff. Concordance between glass slides and WSI ranged from 93% to 100% among various applications on validation. We also provided equal opportunities for every pathologist throughout the department to be competent and confident with DP through prospective validation, with overall concordance of 96% compared with glass slides, allowing appreciation of the advantages and limitations of WSI, hence enabling the use of DP as a useful diagnostic modality. Conclusions: Smooth integration of DP into the diagnostic laboratory is possible with careful planning, discipline and a systematic approach adhering to our guiding principles.